DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI DKI JAKARTA - Valencia Christmas Manus; Meiriska Febrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research purpose is to obtain empirical evidence of the e-filling application, tax socialization, tax sanctions, service quality of tax authorities, realization of tax payers, and e-billing application for the compliance of personal tax payers in DKI Jakarta. The data collecting in this research used the questionnaire through google form. The number taken as samples for this research is 100 personal tax payer respondents in DKI Jakarta. The method used in selecting the samples is convenience sampling.The result showed that the e-filling application, tax sanctions, service quality of tax payers, realization of tax payers, and e-billing application don’t affect the compliance tax payers, meanwhile the socialization affects the compliance of tax payers. Taxpayer who understand the tax information through socialization activities will determine the attitude of taxpayers in carrying out their tax obligation.